How can African agriculture adapt to climate change: Risk aversion in low-income countries: Experimental evidence from Ethiopia - Yesuf, Mahmud; Bluffstone, Randy (International Food Policy Research Institute, 2008)
Agricultural production remains the main source of livelihood for rural communities in Sub-Saharan Africa, providing employment to more than 60 percent of the population and contributing about 30 percent of gross domestic product. With likely long-term changes in rainfall patterns and shifting temperature zones, climate change is expected to significantly affect agricultural production, which could be detrimental to the region’s food security and economic growth. An assessment of the factors influencing farm-level adaptation can facilitate the formation of policies and investment strategies that help moderate potential adverse consequences of long-term climate change. Because smallholder farmers tend to have a low capacity to adapt to changes in climatic conditions, policies that help these farmers adapt to global warming and associated climatic extremes are particularly important. This brief is based on a study that assesses smallholder farmers’ adaptation to climate change in southern Africa. The study identifies farmers’ perceptions of climate change and the determinants of farm- evel adaptation strategies, and recommends policies that could help stabilize national and regional food production given the anticipated adverse effects of climate change.